Network disruption detected in VE (Venezuela) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity mixed detected in Venezuela. Data sourced from CensoredPlanet, IODA.
Censorship Incident ID: VE-2026-0004. Severity: critical. Confidence: 70%